Pembentukan Karakter di SDN Kertaungaran Melalui Konsep Pembelajaran Ki Hajar Dewantara - Azmi, Muhammad Fahmi Ulul; Nurfirdaus, Nunu; Nuraeni, Leni (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to find out the formation of character in SDN Kertaungaran through the learning concept of Ki Hajar Dewantara. This study uses a qualitative approach with a case study method of 13 research subjects who were selected using the purposive sampling technique. The data analysis technique uses the miles and huberman model. Data analysis is carried out with the stages of data reduction, data presentation, and conclusion drawn.  Data collection is carried out through observation, interviews, and documentation. Interviews were conducted with school principals, lower grade teachers and higher-grade teachers and lower grade students and high-grade students at SD Negeri Kertaungaran. The results of the analysis show that the character at SDN Kertungaran through the learning concept of Ki Hajar Dewantara has been well embedded. Just as the teacher has set a good example for the students, it also gives encouragement to the students. The roles of family, school, and community all synergize to shape the character of students. Other activities such as religious activities, learning evaluations and integration of local culture can also shape students' character. Learning sports, sports, and sports play a role in improving the character of discipline, cooperation, and responsibility. Schools must stick to the learning concept of Ki Hajar Dewantara and practice it gradually and consistently.